Exploring HLA-C methylation patterns and nutritional status in Kichwa mothers and infants from Tena, Ecuador - Velastegui, Erick; Falconí, Isaac B.; Garcia, Valeria I.; Munizaga, Gabriela; Matias de la Cruz, Carmen; Segura, Yaritza; Alcivar, Kerly; Valencia, Luz; Vera, Edwin; Muñoz, Mindy S.; Vanden Berghe, Wim; Lebeer, Sarah; et al. (Frontiers in Medicine, 2024)
Environment and lifestyle can affect the epigenome passed down from generation to generation. A mother's nutrition can impact the methylation levels of her offspring's epigenome, but it's unclear which genes may be affected by malnutrition during gestation or early development. In this study, we examined the levels of methylated GC in the promoter region of HLA-C in mothers and infants from the Kichwa community in Ecuador. To do this, we analyzed saliva samples using bisulfite DNA sequencing. While we did not observe any significant differences in the mean methylation percentages in exon 1 of HLA-C between mothers and their infants after the first two years of lactation and life, respectively, we did find that infants tended to increase their methylation level during the first two years of life, while mothers tended to decrease it after the first two years of breastfeeding. When we compared methylation levels between mothers and infants using an ANOVA/posthoc Tukey test, we found that the average methylation for the entire population was less than 3% at T1 and T2. Although there was a tendency for infants to have higher methylation levels during their first two years of life and for mothers to have lower methylation levels after the first two years of breastfeeding, the mean values were not significantly different. However, we found a significant difference when we contrasted the data using a Kruskal-Wallis test at 0.05 for T1 AND T2 (p-value: 0.0148). Specifically, mothers had an average of X̅= 2.06% and sons had X̅=1.57% at T2 (p-value: 0.7227), while the average for mothers was X̅= 1.83% and for sons X̅=1.77%. Finally, we identified three CpG motif nucleotide positions (32-33, 43-44, and 96-97) along the 122 bp analysis of HLA-C exon one, which was found to retain methylation patterns over time and is inherited from mother to offspring. Finally, our small pilot study did not reveal significant correlations between maternal and offspring nutritional status and DNA methylation levels of HLA-C exon one.